The Influence of Internal and External Factors on the Purchase Decision of Bagged Cement in Java Island - Rahmah, Ayu Annisa; Yuliati, Lilik Noor; Taryana, Asep (International Journal Labs, 2025)
This study aims to analyze the influence of internal and external factors on the purchase decision of bagged cement in Java Island. The research focuses on identifying how consumer characteristics, purchasing power, and brand perception (internal factors) interact with price competition, distribution networks, and promotional strategies (external factors) in shaping purchasing behavior. Using a quantitative approach with survey data collected from cement buyers across several provinces in Java, the study employs multiple regression analysis to examine the relationship between these variables. The results indicate that both internal and external factors significantly affect purchasing decisions, with external factors such as price and distribution showing the strongest influence. Meanwhile, internal factors like brand loyalty and consumer preference also play a substantial role, particularly in urban markets. The findings contribute to a better understanding of consumer behavior in the cement industry and provide practical implications for manufacturers and distributors to optimize their marketing strategies and maintain competitiveness in one of Indonesia’s largest cement markets.